On Annual Cycle of Monogenean Parasites Infestation in Freshwater Fish Pangasius pangasius - Sharma, Ruchi; ., Deepa; Tyagi, Shelly; Panwar, Anju; Panwar, Anju; Kumar, Satyendra; Tyagi, Charu; Kumar, Yougesh (The Scientific Temper, 2020)
Annual cycle on the infestation of monogenean parasites found in fresh water fish Pangasius pangasius is statistically analysed and presented in this communication. During routine course of investigations for the presence of helminth parasites harbouring freshwater fishes found in Muzaffarnagar, annual data was collected for these parasites. Results are well presented in the form of tables. Statistical analysis of the data is carried for density, intensity, rate of infestation and the same has been correlated for annual cycle